Investigation of residual stress in selective laser melting - Parry, Luke Alexander (2018)
Selective laser melting is an attractive technology, enabling the manufacture of customised, complex metallic designs, with minimal wastage. However, uptake by industry is currently impeded by several technical barriers, such as the control of residual stress, which have a detrimental effect on the manufacturability and integrity of a component. Indirectly, these impose severe design restrictions and reduce the reliability of components, driving up costs.